Menyikapi Kehadiran Siswa Berkebutuhan Khusus dalam Pembelajaran Sejarah di Kelas: Perbandingan Sekolah Inklusi dan Non-inklusi - Halim, Wardatul Haifa Syafira; Kusmarni, Yani; Wiyanarti, Erlina (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2020)
The characteristic of history subject are consist of facts to implement the significance of past event presented in the learning process, it probably leads student toward attitude transformation. Those opportunities should be provided to all student, including for those whose special needs. The emergences of 17s sustainable development goals (no. 4: Quality Education) has created multiple platforms to carry out inclusive education, including during history learning process. This article uses descriptive study method to get in-depth explanation about history learning process in a set of inclusive education implementation by comparing the condition between inclusive school and non-inclusive school. The result showed (1) lack of understanding of history teacher in identify special needs students has becoming the main bottleneck during learning process; (2) lack of history teacher’s capability in arranging PPI (Individual Learning Program) for special needs students; (3) supporting teacher’s unavailability in helping history teacher during learning process.